Influence of polymeric nanowire topography on the differentiation of adipose-derived stem cells - Trujillo, Nathan Anthony, author; Popat, Ketul, advisor; Williams, John, committee member; Dasi, Lakshmi Prasad, committee member; Kipper, Matt, committee member (Colorado State University. Libraries, 2014)
Considering the many advances in tissue engineering, there are still significant challenges associated with restructuring, repairing, or replacing damaged tissue in the body. Recently biodegradable synthetic scaffolds have shown to be a promising alternative. However, based on the application, it is essential that the scaffold possess specific surface properties that promote cell-scaffold interactions and aid in extracellular matrix deposition. In this work, we present a novel solvent-free, template-synthesis technique for creating substrate-bound nanowire scaffolds from polycaprolactone, a biocompatible and biodegradable polymer. Nanowire surfaces were also fabricated from polycaprolactone that included 1 wt% hydroxyapatite nanoparticles for osteogenic studies. The fundamental concept behind successful synthetic tissue-engineered scaffolds is to promote progenitor cell migration, adhesion, proliferation, and induce differentiation, extracellular matrix synthesis, and finally integration with host tissue. Recently, lipoaspirate tissue has been identified as a viable alternative source for mesenchymal stem cells because it contains a supportive stroma that can easily be isolated. Adipose derived stem cells can differentiate into a variety of mesodermal lineages including the osteogenic, chondrogenic, and adipogenic phenotypes. The results indicated that during the growth period i.e., initial 7 days of culture, the nanowire surfaces supported adhesion, proliferation, and viability of the cells in addition to morphological changes. Osteogenic, chondrogenic, and adipogenic differentiation potential of adipose derive stem cells was evaluated with and without differentiation supplements to determine the influence of nanowire architecture on mechanotrasnduction. It was determined that nanowire topography stimulated the expression of osteogenic marker proteins, osteocalcin and osteopontin, as well as mineralization and alkaline phosphatase activity.
Keywords: adipogenic; chondrogenic; nanowires; osteogenic; polycaprolactone; stem cells